Study of the Influence of Thermal Annealing of Ga-Doped ZnO Thin Films on NO2 Sensing at ppb Level - Benjamin Paret; Richard Monflier; Philippe Menini; Thierry Camps; Yohann Thimont; Antoine Barnabé; Lionel Presmanes (Chemosensors)
In this paper, the sensitivity to sub-ppm NO2 concentration of 50 nm thick Ga-doped ZnO (GZO) films grown by RF magnetron sputtering is studied. The films were annealed under dry air for 4 h at either 500 °C, 600 °C, or 700 °C. The increase in the annealing temperature leads to an improvement of the crystallinity while no significant evolution of the surface grain size is observed. The electrical resistance of the thin films was measured at 250 °C under neutral argon atmosphere, humid air reference atmosphere, and reference atmosphere polluted by 100 ppb of NO2. An increase in sensitivity to NO2 is noted for samples annealed at 600 °C, leading to a response RNO2/Rair of ~10 for 100 ppb of NO2. Finally, photoluminescence spectra are compared with their electrical resistance at 250 °C under the various atmospheres to understand this phenomenon. It is proposed that the origin of the NO2 maximum sensitivity for films annealed at 600 °C is the consequence of a specific annihilation of point defects resulting in an increase in the relative concentration of oxygen vacancies, which improves selectivity toward NO2.